Post-treatment adaptation experiences of women breast cancer survivors: a qualitative study - Bayrak, Nisa Yavuzer; Ozcan, Serpil; Turan, Gulcan Bahcecioglu (Springer, 2026)
ObjectiveThis study was conducted to explore breast cancer survivors' experiences with their adjustment process.MethodThe study population included women registered at a university hospital who had completed active treatment (surgery, chemotherapy, and/or radiotherapy) between May and July 2025, including those continuing hormone therapy. The study sample included 20 women who agreed to participate. The criterion sampling method was employed. The research data were collected through 'Introductory Information Form', 'Semi-structured Questionnaire', and face-to-face individual interviews. Interviews were recorded with a voice recorder, with the participants' permission. The content analysis method was used to evaluate the qualitative data. In the study, the COREQ (Consolidated Criteria for Reporting Qualitative Research) Checklist was used to report qualitative research.ResultsAs a result of the analysis of the data obtained from the interviews on the experiences of breast cancer survivors regarding the adaptation process, five themes, namely Difficulties in the Adaptation Process, Emotional Experiences, Coping Strategies, Change in Lifestyle and Self-Perception and Support Mechanisms in the Adaptation Process, and a total of 34 codes for these themes were created.ConclusionThe findings showed that women experienced physical and emotional challenges during the adaptation process, including fatigue, weakness, limited mobility, and emotional confusion. Coping strategies included appearing strong and relying on trust and gratitude. Women also reported changes in lifestyle, self-perception, and life perspective, with a greater focus on living in the moment and self-care. Family members, especially children and spouses, were identified as the main sources of support.
Keywords: Breast neoplasms; Cancer survivors; Adaptation; Psychological; Coping behavior; Social support; Qualitative research